Integrals of Chebyshev polynomials of third and fourth kinds: An application to solution of boundary value problems with polynomial coefficients - E. H. Doha; W. M. Abd-Elhameed (Հայաստանի ԳԱԱ)
Two new formulae expressing explicitly the repeated integrals of Chebyshev polynomials of third and fourth kinds of arbitrary degree in terms of the same polynomials are derived.
Keywords: Mathematics; Science